Kearns–Sayre syndrome presenting with progressive external ophthalmoplegia and third-degree atrioventricular block diagnostic challenge in resource-limited settings: a case report - Gebeyehu Tessema Azibte; Zekarias Seifu Ayalew; Bereket Abraha Molla; Meseret Zewdie Ayele; Temesgen Baylie Bezabeh; Surafiel Adugna Wube; Biruk Abate Legesse; Tigist Kahsay Meresa (Journal of Medical Case Reports)
Abstract Background Kearns–Sayre syndrome is a rare autosomal recessive mitochondrial disorder characterized by progressive external ophthalmoplegia and pigmentary retinopathy. Onset typically occurs before the age of 20 years and is attributed to mutations within mitochondrial DNA affecting proteins critical for the oxidative phosphorylation pathway. Since these mitochondrial disorders usually present with an isolated manifestation such as complete heart block, a meticulous search for other organ-specific manifestations is necessary for an early diagnosis. Reporting such cases facilitates recognition of common clinical presentations, enabling earlier diagnosis, earlier interventions, and genetic counseling. Case presentation A 29-year-old right-handed Ethiopian male patient presented with progressive exercise intolerance for 10 years. He had had bilateral ptosis since childhood and experienced gait difficulty with intermittent balance problems, particularly at night. In 2018, he was diagnosed with a third-degree atrioventricular block with a resting electrocardiogram, and a permanent pacemaker was placed. Despite marked improvement in shortness of breath following pacemaker placement, the patient’s progressive ptosis and gait ataxia prompted further workup, ultimately leading to the diagnosis of Kearns–Sayre syndrome. This case highlights the importance of comprehensive assessment in patients presenting with isolated organ manifestations, as exemplified by the delayed diagnosis of Kearns–Sayre syndrome following the initial recognition of a complete heart block. Conclusion Given the early-onset nature of Kearns–Sayre syndrome, it should be considered as a differential diagnosis in young individuals presenting with complete heart block. A thorough evaluation for additional organ involvement is crucial in such cases, as early intervention and genetic counseling significantly impact patient outcomes.